Alonso's General Theory of Movement: Advances in Spatial Interaction Modeling - Jacob J. de Vries; Peter Nijkamp; Piet Rietveld (Tinbergen Institute, 2000)
The Spatial Interaction Model proposed by Alonso as Theory ofMovements offers a new specification of spatial origin-destination flow models. Equations for flows between regions, totaloutflow from and total inflow to a region are linked bybalancing factors. The paper presents a consistent formulation ofSpatial Interaction Models in the Wilson tradition andAlonso's General Theory of Movement. It will be demonstrated thatAlonso's model contains Wilson's Family of SpatialInteraction Models as special cases, but that the reverse is nottrue. The paper discusses interpretations of the model andanalyzes its statistical properties. Several approaches will bediscussed which aim to make the meaning of the balancingfactors more explicit. The paper shows that simultaneous equationtechniques are required to estimate the variousrelevant parameters.
Keywords: 330; Binnenwanderung; Theorie; Mobilität